1993
DOI: 10.1111/j.1399-0004.1993.tb03910.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease profile of 400 institutionalized mentally retarded patients in Kuwait

Abstract: Farag TI, Al‐Awadi SA, El‐Badramary MH, Aref MA, Kasrawi B, Krishna Murthy DS, El‐Khalifa MY, Yadav G, Marafie MJ, Bastaki L, Wahba RA, Mohammed FM, Abul Hasan S, Redha AA, Redha MA, Al‐aboud H, Al‐Hijji S, Al‐Dighashem D, Al‐Hashash N, Al‐Jeeryan L, Al‐Khor‐afi H, Qurban EA, Al‐Sulaiman I. Disease profile of 400 institutionalized mentally retarded patients in Kuwait. Clin Genet 1993: 44: 329–334. © Munksgaard, 1993 In this preliminary report we summarize the results of a 4‐year multidisciplinary systematic, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Although he mainly focused on inheritance patterns and looking at nature versus nurture effects, he also reported congenital malformations in this cohort. Despite almost a century of additional research, of which many reported on associated clinical features in individuals with NDD [2][3][4][5][6][7][8][9][10][11][12][13][14][15], only the prevalence of comorbid mental health disorders and epilepsy (respectively up to 40% and 26%) have been determined [16,17]. For most specific phenotypic characteristics the overall prevalence, however, eludes us, although these additional phenotypic features are essential when taking care of a child with developmental delay (DD) or intellectual disability (ID).…”
Section: Introductionmentioning
confidence: 99%
“…Although he mainly focused on inheritance patterns and looking at nature versus nurture effects, he also reported congenital malformations in this cohort. Despite almost a century of additional research, of which many reported on associated clinical features in individuals with NDD [2][3][4][5][6][7][8][9][10][11][12][13][14][15], only the prevalence of comorbid mental health disorders and epilepsy (respectively up to 40% and 26%) have been determined [16,17]. For most specific phenotypic characteristics the overall prevalence, however, eludes us, although these additional phenotypic features are essential when taking care of a child with developmental delay (DD) or intellectual disability (ID).…”
Section: Introductionmentioning
confidence: 99%